The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0030161
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Eddies Are Oases for Higher Trophic Marine Life

Abstract: Mesoscale eddies stimulate biological production in the ocean, but knowledge of energy transfers to higher trophic levels within eddies remains fragmented and not quantified. Increasing the knowledge base is constrained by the inability of traditional sampling methods to adequately sample biological processes at the spatio-temporal scales at which they occur.By combining satellite and acoustic observations over spatial scales of 10 s of km horizontally and 100 s of m vertically, supported by hydrographical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
144
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(166 citation statements)
references
References 51 publications
14
144
3
Order By: Relevance
“…Mesoscale eddies, such as the Capricorn Eddy, stimulate and redistribute biological production in the ocean, thus creating attractive pelagic habitats for free-ranging, higher trophic level marine organisms (Chelton et al 2011, Godø et al 2012. Our results suggest that manta rays may exploit offshore mesoscale eddies for foraging purposes and corroborate several other studies that showed the importance of mesoscale eddies as offshore foraging grounds for a variety of marine species (e.g.…”
Section: Eddy Affinity and Offshore Foragingsupporting
confidence: 87%
“…Mesoscale eddies, such as the Capricorn Eddy, stimulate and redistribute biological production in the ocean, thus creating attractive pelagic habitats for free-ranging, higher trophic level marine organisms (Chelton et al 2011, Godø et al 2012. Our results suggest that manta rays may exploit offshore mesoscale eddies for foraging purposes and corroborate several other studies that showed the importance of mesoscale eddies as offshore foraging grounds for a variety of marine species (e.g.…”
Section: Eddy Affinity and Offshore Foragingsupporting
confidence: 87%
“…These filaments, which correspond to frontal transportation, are reported to carry high zooplankton densities (Labat et al, 2009;Perruche et al, 2011), which may explain why seals are more likely to increase search intensity in response to sites of elevated plankton densities, even throughout winter. Cotté et al (2014) also suggest that seals may temporally exploit these rich filaments while also using them to track the most profitable meso-scale features where higher prey densities occur (e.g., eddies- Godo et al, 2012). This is consistent with our results which showed seals foraging in winter were more likely to spend greater time foraging at depth and increase foraging success in response to elevated plankton densities.…”
Section: Seasonally-contrasted Foraging Strategies In Relation To Ressupporting
confidence: 88%
“…This is consistent with our results which showed seals foraging in winter were more likely to spend greater time foraging at depth and increase foraging success in response to elevated plankton densities. Strong meandering meso-scale eddies created by the energetic ACC (Chelton et al, 2007) are thought to facilitate plankton accumulation (Godo et al, 2012) and retention times long enough to transfer energy to different trophic levels (Biggs, 1992;Riandey et al, 2005;Benitez-Nelson and McGillicuddy, 2008), including fish (e.g., Nishimoto and Washburn, 2002;Zainuddin et al, 2006) and apex predators such as SESs (d 'Ovidio et al, 2013). These advected water parcels are thought to sustain the pelagic ecosystem east of its origin and could explain the progressively eastward displacement of winter foraging seals.…”
Section: Seasonally-contrasted Foraging Strategies In Relation To Resmentioning
confidence: 99%
“…This heat loss is important since anomalous heat transported by the slope current downstream of the Lofoten Basin is found to influence the sea ice cover in the Barents Sea (Sandø et al 2010;Årthun et al 2012) and the regional climate of Svalbard (Walczowski and Piechura 2011). Furthermore, mesoscale eddies in the basin are found to provide a rich feeding habitat for higher trophic marine life (Godø et al 2012). Thus, similar to other regions of the world oceans (e.g.…”
Section: Introductionmentioning
confidence: 99%